Features of Resting-State Electroencephalogram Theta Coherence in Somatic Symptom Disorder Compared With Major Depressive Disorder: A Pilot Study. Issue 9 (November 2017) - Ahn, Jaeyoung; Han, Doug Hyun; Hong, Ji Sun; Min, Kyoung Joon; Lee, Young Sik; Hahm, Bong-Jin; Kim, Sun Mi
ABSTRACT: Objective: Somatic symptom disorder (SSD) often co-occurs with major depressive disorder (MDD). Both conditions share common psychobiological and biobehavioral characteristics, but little is known about differential patterns in brain function. In this study, we compared resting-state functional brain connectivity between SSD and MDD using quantitative electroencephalography. Methods: Fifteen patients with SSD (SSD group), 15 patients with MDD (MDD group), and 15 healthy volunteers (healthy control [HC] group) participated in this study. Participants were assessed with quantitative electroencephalography using a 21-channel electroencephalogram system. Electroencephalogram coherence in the theta frequency range (3.5–7.5 Hz) was assessed between the following seven electrode pairs: Fp1 and Fp2, F7 and T3, F8 and T4, T5 and P3, P4 and T6, P3 and Pz, and Pz and P4. Differences in coherence between groups were analyzed using analysis of variance. Results: Theta coherence between the F7 and T3 electrodes was lower in the SSD group than the MDD and HC groups ( F (2, 42) = 6.67, p = .0030). Theta coherence between the T5 and P3 electrodes was lower in the SSD and MDD groups than the HC group ( F (2, 42) = 5.65, p = .0067). Theta coherence between the Pz and P4 electrodes was lower in the SSD group than the MDD group ( F (2, 42) = 6.41, p = .0037). Conclusions: Both SSD and MDD patients commonly showed decreased functional connectivity within the left temporoparietal junction, which has neurophysiological implications for cognitive-attentional processing and social interaction. Frontostriatal circuit dysfunction affects processes that control perception and emotion, as well as misperception of somatosensory data in the parietal somatosensory area, and is more likely to be a neuropathology of SSD than MDD.